Uji Resistensi Vektor Demam Berdarah Dengue (DBD) Terhadap Insektisida Permethrin di Kota Binjai Provinsi Sumatera Utara Tahun 2022 - Indah Anggraini; Ledy Afrida Sinaga; Ahadi Kurniawan (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
The control effort of Dengue Hemorrhagic Fever (DHF) which is transmitted by the Aedes sp. infected with the Dengue virus, of which can be done by fogging. The active ingredient for fogging generally uses the insecticide permethrin. This study aimed to identify the resistance status of DHF vectors to the insecticide permethrin in controlling DHF vectors. The method of collecting Aedes sp. larvae was carried out in 100 residents' houses in neighborhoods 3 and 4 of Damai Village, North Binjai District, Binjai City, North Sumatra Province by observing each water reservoir that has the potential to become a breeding ground for Aedes sp. Aedes sp. larvae colonized until the F1 generation, then tested for resistance to permethrin insecticide using the CDC Bottle method. Data analysis was carried out descriptively. The percentage of death of test mosquitoes was 25% (<80%). It was concluded that the Aedes sp. in Neighborhoods 3 and 4 of Damai Village, North Binjai District, Binjai City were resistant to the insecticide permethrin. It is recommended that the Binjai City Health Office/Government make a policy in controlling the DHF vector by replacing Permethrin insecticide with another class of insecticides.